Preparedness for Mass Casualty Incidents: The Effectiveness of Current Training Model. (29th October 2022) - Biswas, Seema; Bahouth, Hany; Solomonov, Evgeny; Waksman, Igor; Halberthal, Michael; Bala, Miklosh
Abstract: The importance of MCI organization and training was highlighted by the events of September 11, 2001. Training focuses on the management of physical injuries caused by a single traumatic event over a well-defined, relatively short timeframe. MCI management is integrated into surgical and trauma training, with disaster management training involving the emergency services, law enforcement, and state infrastructure agencies. The COVID-19 pandemic revealed gaps in the preparedness of nation states and global partners in disaster management. The questions that arose include 'has training really prepared us for an actual emergency, ' 'what changes need to be made to training to make it more effective, ' and 'who else should training be extended to?' This article focuses on the importance of involving multiple sectors in mass casualty training and asks whether greater involvement of non-medical agencies and the public, in operational drills might improve preparedness for global events such as the COVID-19 pandemic.